A Study of the Effectiveness of Influenza Vaccination in an Industrial Population. Issue 3 (July 1962) - Meichen, F. W.; Rogan, E.; Howell, R. W.
Abstract : In November 1960, influenza vaccination was offered to an industrial population. Some 2, 500 volunteers indicated that they wished to take advantage of it. Due to the nature of the reactions experienced by vaccinated personnel, this number fell to 1, 850. This study compares the sickness absence of vaccinated and non-vaccinated groups due to influenza, bronchitis, and other respiratory causes, during the ensuing winter months. The vaccinated group appeared to derive a moderate degree of immunity, particularly in the age group over 45 years, but some effort should be made to minimize the reaction caused by the vaccine.